The function of plasma membrane V-ATPases in breast cancer metastasis - Li, Zhen. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023-05.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisors: Michael Forgac, and James Baleja.; Keywords: Pharmacology, Oncology, and Developmental biology.